Antioxidant Therapy in Graves’ Orbitopathy - Lanzolla, Giulia; Marcocci, Claudio; Marinò, Michele (Frontiers in Endocrinology, 2020)
The balance of the cell redox state is a key point for the maintenance of cellular homeostasis. Increased reactive oxygen species (ROS) generation leads to oxidative damage of tissues, which is involved in the development of several diseases, including autoimmune diseases. Graves’ Orbitopathy (GO) is a disfiguring autoimmune-related condition associated with Graves’ Disease (GD). Patients with active, moderate-to-severe GO, are generally treated with high doses intravenous glucocorticoids (ivGCs) and/or orbital radiotherapy. On the contrary, up to recently, local ointments were the treatment most frequently offered to patients with mild GO, because the risks related to ivGCs does not justify the relatively poor benefits expected in mild GO. However, a medical treatment for these patients is heavily wanted, considering that GO can progress into more severe forms and also patients with mild GO complain with an impairment in their quality of life. Thus, based on the role of oxidative stress in the pathogenesis of GO, a therapy with antioxidant agents has been proposed and a number of studies have been performed, both in vitro and in vivo, which is reviewed here.